Assessment of Inflammatory Biomarkers as Predictor of Mortality in COVID-19 Patients - Muhammad Mansoor Hafeez, Muhammad Tahir Khan, Tania Ahmed Shakoori, Waqas Mahmood, M. Sohail Khalid, M. Asim Rana, Sitara Raza (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In individuals with coronavirus, a cytokine storm is an important cause of illness and demise. The purpose of the study was to assess whether pro-inflammatory cytokines had an impact on progression and risk of mortality in patients with COVID-19. Study Design: Retrospective study Place and Duration of Study: Intensive Care Unit (ICU) and Medical Wards, Bahria Town International Hospital from 21st August 2020 to 17th September 2021. Methodology: One hundred and thirty-six patients of confirmed cases of COVID-19 disease were enrolled. Their demographic, blood and biochemical parameters were collected within 48 hours after admission from the medical record of patients. Patients were divided into two groups according to the final outcome, the survivors and non survivors. The data were investigated to assess the prognostic importance of the blood marker and inflammatory variables for the prognostic importance. Results: The mean age and body mass index (BMI) were statistically higher in the non-survivors than in the survivors (p=0.017 and 0.03 respectively). For those with asthma and chronic obstructive pulmonary disease, the number was statistically higher in non-survivors (p = 0.002 and 0.04, respectively). The inflammatory markers concentrations of CPR, D. Dimer, serum ferritin, procalcitonin, and interleukin-6 were significantly higher within 48 hours of admission for non-survivors (p = 0.003, 0.007, <0.001, 0.015, and <0.001 respectively). Except ferritin levels, multi-variate logistic regression analysis exhibited that the CRP, D. Dimer, Procalcitonin and IL-6 were associated statistically significant higher risk of mortality (OR 1.235, p=0.007, 95% Cl 5.621-42.652, OR 1.906, p=0.003, 95% Cl 1.481-1.982, OR 3.967, p=<0.001, 95% Cl 4.256-23.981, and OR 7.589, p=0.009, 95% Cl 4.561-113.852 respectively). Conclusion: The inflammatory markers have the prognostic importance in patients suffering from covid-19 infection as we found higher levels of these markers were related with the poor prognosis.